The African citrus psyllid Trioza erytreae: An efficient vector of Candidatus Liberibacter asiaticus - Reynaud, Bernard; Turpin, Patrick; Molinari, Florencia M.; Grondin, Martial; Roque, Solène; Chiroleu, Frédéric; Fereres, Alberto; Delatte, Hélène (Frontiers in Plant Science, 2022)
Introduction Huanglonbing (HLB) is the most serious disease of citrus in the world, associated with three non-cultivable phloem-restricted bacteria Candidatus Liberibacter asiaticus (CLas), Ca L. africanus (CLaf) and Ca L. americanus (CLam). CLas is transmitted by the Asian citrus psyllid Diaphorina citri, and has spread to several countries. The African psyllid Trioza erytreae, the vector of CLaf occurs in Africa and neighbouring islands. Only two major citrus-growing regions - Australia/New Zealand and the Mediterranean Basin - are still HLB-free in the world. However, T. erytreae has recently been introduced into continental Europe (Portugal and Spain) and has become a potential threat to citrus production. The transmission of CLas by T. erytreae had been postulated but never tested. To evaluate the risk of T. erytreae transmitting CLas, comparative transmissions of CLas by T. erytreae and D. citri were assessed. Methods Transmission tests were performed on excised leaves and seedlings of Citrus volkameriana with different inoculation access periods (in series) for both insect species. Quantifications of bacterial titers were made in excised leaves, seedlings three and six months after inoculation and on individual insects. Results Our results showed that T. erytreae was able to efficiently acquire CLas. Furthermore, T. erytreae carried significantly higher bacterial titers than D. citri, and was able to efficiently transmit the bacteria to seedlings at a similar rate that D. citri highlighting the high risk of spread of the most aggressive variant of HLB (CLas) by T. erytreae in Europe. Discussion Thus, extreme precautions to prevent any entry of CLas into Europe should be adopted.